Recovering Keynesian Phillips Curve Theory: Hysteresis of Ideas and the Natural Rate of Unemployment - Thomas Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
Economic theory is prone to hysteresis. Once an idea is adopted, it is difficult to change. In the 1970s, the economics profession abandoned the Keynesian Phillips curve and adopted Milton Friedman's natural rate of unemployment (NRU) hypothesis. The shift was facilitated by a series of lucky breaks. Despite much evidence against the NRU, and much evidence and theoretical argument supportive of the Keynesian Phillips curve, the NRU hypothesis remains ascendant. The hypothesis has had an enormous impact on macroeconomic theory and policy. 2018 is the fiftieth anniversary of Friedman's introduction of the NRU hypothesis. The anniversary offers an opportunity to challenge, rather than celebrate it.
Keywords: E00; E12; E20; E30; E60; 330; Natural rate of unemployment; Keynesian Phillips curve; Friedman; Tobin